Documentation and ethnobotanical survey of wild edible plants from Palghar District - SHIVPRASAD, MAHADKAR; RANE, MEGHA; SATAVI, VAIBHAV (Asian Journal of Pharmaceutical and Clinical Research, 2016)
The present study deals with the identification, documentation and ethno-botanical exploration with respect to food value of wild edible plants from Palghar district. Total 40 wild edible plants were documented. Out of them 20 plants are used as a leafy vegetables; fruits of 3 plants are edible, flowers of 7 plants are edible, tubers of 10 plants are edible. Edible parts of wild plants (fruit, flower, leaves, tubers and inflorescences) are the nature's gift to mankind; these are not only delicious and refreshing but also the chief source of vitamin, minerals and protein. The wild edible plants are the normal food of cattle grazers and the forest tribes. Although the popularity of these wild forms of fruits, flowers and tubers has declined, it is considered that special attention should be paid to them in order to maintain and improve this important source of food supply. Key word: Wild edible plant, Palghar district, ethnobotany.